TTBK1 and CK1 inhibitors restore TDP-43 pathology and avoid disease propagation in lymphoblast from Alzheimer’s disease patients - Martinez-Gonzalez, Loreto; Cuevas, Eva P.; Tosat-Bitrián, Carlota; Nozal, Vanesa; Gil, Carmen; Palomo, Valle; Martín-Requero, Ángeles; Martinez, Ana (Frontiers in Molecular Neuroscience, 2023)
TDP-43 proteinopathy in Alzheimer's disease (AD) patients is recently emerging as a relevant pathomolecular event that may have been overlooked. Recent results in immortalized lymphocytes from AD patients have shown not only an increase of post-translational modifications in TDP-43, such as hyperphosphorylation and fragmentation, but also its prionic behaviour and cell-to-cell disease transmission. In this work, we present different kinase inhibitors with therapeutic potential in this pathological mechanism. We deepened the study in the TDP-43 pathology and transmission through conditioned medium (CM) experiments based on the incubation of lymphoblasts derived from healthy individuals with CM from severe AD patients with and without a previous treatment with TTBK1 and CK1 inhibitors. U2OS cells treated with CM from severe AD patients were also used to study cytosolic transport using kinesin fluorescent probes. TDP-43 pathology, including increased phosphorylation and cytoplasmatic localisation, observed in lymphoblasts from severe AD patients is reduced after the treatment with TTBK1 and CK1 inhibitors. Furthermore, a significant increase in TDP-43 phosphorylation and cytoplasmic accumulation as well as aberrant F-actin protrusions (TNT-like This is a provisional file, not the final typeset article structures) in control cells growing in CM from AD lymphoblasts was observed. In addition, a dynamic functionality of the receptor cells, cytosolic transport mediated by molecular motors was altered. All these pathological changes were not observed when the CM from AD lymphoblasts treated with previously reported TTBK1 and CK1 inhibitors, VNG1.47 and IGS2.7, respectively, were used to incubate the lymphoblast of healthy controls. In that situation, prevention of TNT-like structures formation and normalization of cytosolic transport has also been confirmed. The TTBK1 and CK1 inhibitors, VNG1.47 and IGS2.7, restore TDP-43 pathology and avoid cell-to-cell propagation in immortalized lymphocytes from AD patients, being excellent candidates for the future therapy of this devastating disease 1